Durable crystalline Si photovoltaic modules based on silicone-sheet encapsulants. (5th January 2018) - Hara, Kohjiro; Ohwada, Hiroto; Furihata, Tomoyoshi; Masuda, Atsushi
Abstract: Crystalline Si photovoltaic (PV) modules were fabricated with sheets of poly(dimethylsiloxane) (silicone) as an encapsulant. The long-term durability of the silicone-encapsulated PV modules was experimentally investigated. The silicone-based modules enhanced the long-term durability against potential-induced degradation (PID) and a damp-heat (DH) condition at 85 °C with 85% relative humidity (RH). In addition, we designed and fabricated substrate-type Si PV modules based on the silicone encapsulant and an Al-alloy plate as the substratum, which demonstrated high impact resistance and high incombustible performance. The high chemical stability, high volume resistivity, rubber-like elasticity, and incombustibility of the silicone encapsulant resulted in the high durability of the modules. Our results indicate that silicone is an attractive encapsulation material, as it improves the long-term durability of crystalline Si PV modules.